Spillover Effects of Exchange Rates : A Study of the Renminbi - Mattoo, Aaditya; Mishra, Prachi; Subramanian, Arvind (2012)
This paper estimates how changes in China's exchange rates would affect exports from competitor countries in third-country markets -- in other words, the "spillover effect." The authors use recent theory to develop an identification strategy, with a key role for the competition between China and its developing country competitors in specific products and export destinations. Using disaggregated trade data, they estimate the spillover effect by exploiting the variation across different exporters, importers, products, and time periods. They find a spillover effect that is statistically and quantitatively significant. Their estimates suggest that a 10-percent appreciation of China's real exchange rate boosts a developing country's exports of a typical four-digit Harmonized System product category to third markets by about 1.5 to 2 percent on average. The magnitude of the spillover effect varies systematically with the characteristics of products, such as the extent to which they are differentiated.